Measurement of fs/fu variation with proton-proton collision energy and B-meson kinematics - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2020)
The ratio of the B-s(0) and B+ fragmentation fractions f(s) and f(u) is studied with B-s(0) -> J/psi phi and B+ -> J/psi K+ decays using data collected by the LHCb experiment in proton-proton collisions at 7, 8, and 13 TeV center-of-mass energies. The analysis is performed in bins of B-meson momentum, longitudinal momentum, transverse momentum, pseudorapidity, and rapidity. The fragmentation-fraction ratio f(s)/f(u) is observed to depend on the B-meson transverse momentum with a significance of 6.0 sigma. This dependency is driven by the 13 TeV sample (8.7 sigma), while the results for the other collision energies are not significant when considered separately. Furthermore, the results show a 4.8 sigma evidence for an increase of f(s)/f(u) as a function of collision energy.
Im Titel sind die Buchstaben s und u tiefgestellt, "f" ist als mathematisches Zeichen dargestellt
LHCb Collaboration: R. Aaij, S. Bachmann, D. Berninghoff, M. Borsato, S. Braun, A. Comerma-Montells, P. D'Argent, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, M. Kolpin, R. Kopecna, B. Leverington, H. Malygina, J. Marks, D.S. Mitzel, S. Neubert, A. Piucci, N. Skidmore, M. Stahl, S. Stemmle, U. Uwer, A. Zhelezov und 848 weitere
Gesehen am 28.04.2020